(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The idioms of Polish and Ukrainian with the lexical component tongue are analyzed in the article. The semantic meaning and etymological derivation of the given linguistic units are compared. It has been proved illustratively that in both languages the above phraseological units in most cases characterize a human being negatively.